Pemanfaatan Air Pit Lake Tambang Batubara Sebagai Media Tanam Kangkung Sistem Hidroponik - Maharani Rindu Widara; Arrina Khanifa; Chairul Salam M (AMMA : Jurnal Pengabdian Masyarakat, 2025)
This study aims to evaluate the effect of using pit lake water of Mekar Jaya Village with and without the addition of alum on the growth of kale plants in hydroponics. Observations were made every three days to measure plant height, leaf length, and number of leaves per plant, the results of which were presented in tables and line diagrams. The results showed that kale plants using water with alum experienced an average height increase of 2 cm, leaf length of 1-1.5 cm, and number of leaves of 1-4 strands every three days. In contrast, plants without alum showed growth of up to 5 cm in height, 0.4-0.5 cm in leaf length, and 1-2 leaves. Measurement of total plant weight showed that the growth of kale plants without alum was better than those with alum. These findings suggest that the use of alum in pit lake water is less effective in supporting the growth of kale plants in hydroponic systems.